3D mesh displacement strategy to simulate the thermal degradation of materials under atmospheric reentry conditions. (October 2022) - Perron, Nicolas; Dellinger, Nicolas; Prévereaud, Ysolde; Balat-Pichelin, Marianne
Abstract: A three-dimensional strategy to compute mesh displacement following surface recession due to ablation is proposed and implemented in the finite volume material response code MoDeTheC. Due to the application to the thermal degradation of space debris during atmospheric reentry, the strategy developed is based onto a very general formulation that can deal with any mesh topology and object shape without preliminary identification of ablated surfaces. First, a new moving mesh method modifies the grid to take into account changes due to ablation. Subsequently, a shape preservation mesh balancing method redistributes the mesh vertices to maintain the grid quality. Finally, a smoothing algorithm is applied to prevent high frequency mesh oscillations. The new 3D mesh displacement strategy is verified on many 2D and 3D test cases to prove the capabilities of the method. Highlights: 3D explicit boundary surfaces are displaced due to ablation with a new formulation. Boundary vertices are redistributed with a shape-preserving mesh balancing method. Undesirable mesh oscillations are removed with a smoothing method without shape flattening. A combination of two Laplacian operators maintains the mesh quality during large mesh deformations. An extended validation is performed on theoretical test cases.